The bovine papillomavirus type 1 (BPV1) replication protein E1 modulates transcriptional activation by interacting with BPV1 E2. - Le Moal, M A (1994)
The study of bovine papillomavirus type 1 (BPV1) DNA replication has shown that E1 and E2 are the only viral proteins required for this process. Both E1 and E2 interact with the viral origin of replication (ori). The BPV1 E2 protein is also a well-characterized transcriptional regulator. We show in this report that E1 can modulate transcription by interactions with E2. At low concentrations, E1 enhanced the E2-mediated transactivation of heterologous promoters containing the BPV1 ori by promoting cooperative binding of both E1 and E2 to the DNA. In contrast, in the presence of excess E1, transactivation by E2 is repressed. This last process, however, does not require cooperative DNA binding of the two proteins. These results imply that the balance between these two distinct types of interaction is crucial both for control of replication and for early viral transcription.